2022
DOI: 10.33821/635
|View full text |Cite
|
Sign up to set email alerts
|

Manejo multidisciplinario de las metástasis cerebrales

Abstract: Introducción: Las metástasis cerebrales (MC) representan una problemática importante de la salud pública, en promedio el 30% de los pacientes oncológicos desarrollarán MC siendo importante causa de morbilidad, ansiedad y mortalidad. El tratamiento con radioterapia, cirugía y sistémico son los pilares para el tratamiento y han tenido una evolución importante en la última década. Propósito de la revisión: Se proporciona información actualizada en relación a epidemiología, diagnóstico, pronóstico y tratamie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Regarding the risk factors identified in previous studies for the incidence of metastases in the CNS, the following have been reported: males, primary lesion in the head or neck, high Breslow index, high serum DHL level, and ulceration of the primary lesion. 14 , 15 , 16 Contrary, we reported the location with the most significant association with metastases was in the right foot and right leg for lesions in the brain and the eye for metastatic lesions to the spine. Similarly, we did not find ulceration presented any risk in the linear regression analysis but a corresponding histopathological result with nodular melanoma.…”
Section: Discussionmentioning
confidence: 56%
“…Regarding the risk factors identified in previous studies for the incidence of metastases in the CNS, the following have been reported: males, primary lesion in the head or neck, high Breslow index, high serum DHL level, and ulceration of the primary lesion. 14 , 15 , 16 Contrary, we reported the location with the most significant association with metastases was in the right foot and right leg for lesions in the brain and the eye for metastatic lesions to the spine. Similarly, we did not find ulceration presented any risk in the linear regression analysis but a corresponding histopathological result with nodular melanoma.…”
Section: Discussionmentioning
confidence: 56%